The Slamet Riyadi Corridor as an Urban Heritage Landscape in the City of Surakarta - Siska Dwi Utami; Rita Noviani; Mohammad Gamal Rindarjono (Universitas Islam Negeri Sumatera Utara, 2026)
Surakarta is a cultural city facing challenges in its preservation efforts: buildings damaged due to neglect, high urbanization, deterioration of material quality, and a lack of stakeholder involvement. Consequently, research is necessary due to the urgent risk of heritage loss and the need for scientific contributions and innovation. Therefore, this study aims to analyze the Slamet Riyadi Corridor as an urban heritage landscape in the city of Surakarta. This study will examine the corridor as an urban heritage landscape comprising history, tangible heritage, and the relationships among landscape elements. The research employs a qualitative method with data analysis stages including data reduction, data presentation, and drawing conclusions. The findings reveal that many of the heritage sites feature Indische architectural styles that blend Javanese and European elements. The cultural heritage statues were erected after Indonesia’s independence to honor the contributions of prominent figures, with the locations chosen to reflect aspects of their lives. The cultural heritage related to transportation was created by Europeans. The objects described represent three of UNESCO’s categories: historic buildings, urban open spaces, and transportation.